Design Perspective of Environmental Interventions through the Stroop Effect, Juggling, and Volunteering for Successful Ageing and Cognitive Health: A Review - Chuangchai, Warawoot; Raymaekers , Sebastiaan (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Environmental design is one of the solutions that supports the idea of successful ageing as well as cognitive health. Designing with environmental interventions offers opportunities for restoration, maintenance, or even enhancement of cognition, particularly in ageing people. Problems of cognitive health, such as mild cognitive impairment and dementia, are frequently and naturally found in ageing people. Design practices and experimental studies in related fields are moving forward at a rapid pace. However, less data are available in relation to design perspectives for cognitive health in the ageing population. This article reviews the benefits of environmental interventions in enhancing cognitive function for ageing people. Relevant English language documents were searched and reviewed through online databases e.g. Scopus, PubMed, Web of Science, Google Scholar and ResearchGate. In this review, the environmental interventions include both physical and social environment interventions. The physical interventions focus on selective attention and decision-making via the Stroop effect and juggling balls respectively. The social intervention focuses on positive behaviour and benefits related to volunteerism and volunteer activities. This article presents environmental interventions that can be integrated as normal daily activities for ageing people to live healthier and more cognitively enriching lives. These interventions could be used in wellness design strategies and applications for designers. The findings of this review also extend the boundaries of designing for the ageing population as an advantage for specialists. Designing with an understanding of cognitive health in ageing people is beneficial and recommended.